BUDAYA NGELONG SUKU KASONG MANGGARAI DALAM TERANG FILSAFAT DIALOGIS MARTIN BUBER - Agustinus Asman; F.X Eko Armada Riyanto (Jurnal Masyarakat dan Budaya, 2022)
The focus of the discussion of this paper is to explore the meaning and philosophical values behind the Ngelong culture of the Kasong tribe of Manggarai-Flores-NTT. The methodology of the discussion perspective uses phenomenological philosophy, namely, the author works on philosophical issues in the form of local wisdom, especially those concerning relationality with nature and the environment, and at the same time dialogues with Martin Buber’s dialogical philosophical thinking. The approach used to explore the Ngelong culture is a qualitative approach by referring to several literature sources and interviews. The purpose of the discussion of this paper is first, to understand more deeply the philosophical meaning behind the local wisdom of the Ngelong culture of the Kasong Manggarai tribe about Martin Buber’s Dialogue Philosophy.